Roads to poverty. Teodor Herburtt’s parish protocol – a source for a portrait of the pauperized layers in Vilnius in the first half of the nineteenth century (Marginesy, 2021)
The article introduces the issues of pauperism in Vilnius in the first half of the nineteenth century. The source basis is Teodor Herburtt’s parish protocol from the 1840–1848, which is a collection of “poverty testimony” of people who applied for help from Vilnius Charitable Society. The preserved document contains not only the names of the poor in Vilnius, but also identifies the religion, social background, family situation and causes of material decline. Thanks to it, we get to know the beneficiaries of philanthropic help from the privacy side.